Noninvasive and invasive ventilation and enteral nutrition for ALS in Italy. Issue 4 (5th August 2014) - Fini, Nicola; Georgoulopoulou, Eleni; Vinceti, Marco; Monelli, Marco; Pinelli, Giovanni; Vacondio, Paolo; Giovannini, Michele; Dallari, Rossano; Marudi, Andrea; Mandrioli, Jessica
ABSTRACT Introduction: We performed a population‐based study to assess amyotrophic lateral sclerosis (ALS) survival after noninvasive ventilation (NIV), invasive ventilation (IV), and enteral nutrition (EN). Methods: We included patients diagnosed from 2000 to 2009 in Modena, where a prospective registry and a Motor Neuron Diseases Centre have been active since 2000. Results: Of the 193 incident cases, 47.7% received NIV, 24.3% received tracheostomy, and 49.2% received EN. A total of 10.4% of the patients refused NIV, 31.6% refused IV, and 8.7% refused EN. The median survival times after NIV, IV, and EN were 15, 19, and 9 months, respectively. Of the tracheostomized patients, 79.7% were discharged from the hospital; 73.0% were discharged to home. The median survival times for tracheostomized patients who were cared for at home and in nursing homes were 43 and 2 months, respectively. The multivariate analysis demonstrated that the place of discharge was the only independent prognostic factor after IV (P < 0.01). Conclusions: Service organizations may promote adherence to NIV, IV, EN, and influence postprocedure survival. These data may be useful in defining health plans regarding advanced ALS care and in patient counseling. Muscle Nerve 50: 508–516, 2014